Mediating effect of personal and situational characteristics of Arab tourists in Malaysia and their influence on information sources and information channels of tourist information choice strategies - Al-Khateeb, Bilal Ahmad Ali (2015)
Statistics show that the influx of tourists in Malaysia has continued to increase by 14.3%; information sources and information channels have played crucial roles in this regard. However, existing studies are yet to distinguish how information sources and information channels influence information choice strategies of Arab tourists. Therefore, this study examines the mediating effects of personal and situational characteristics on information sources and information channels to provide clearer understanding on how information sources and information channels influence the information choice strategies of Arab tourists. Data was collected from 358 Arab tourists in Malaysia through the self-administered questionnaire procedure, and the data was analysed using the multiple regression analysis. Overall, the study found that information sources and information channels had significant influence on the information choice strategies of the Arab tourists. As for the mediating effects, the study also found that personal characteristics significantly mediate the influence of information sources on the information choice strategies of the Arab tourists. The result showed that situational characteristics significantly mediate the influence of information sources on the information choice strategies of the Arab tourists. Therefore, the study concluded that information sources and information channels influence the information choice strategies of the Arab tourists, while personal and situational characteristics significantly mediate influence of the information sources and information channels on the information choice strategies. The study contributes to the body of literature in this area and also provides several insights that may contribute to the development of knowledge that would effectively enhance the tourism industry in Malaysia and also attract more Arab tourists to Malaysia. The study recommends that both the Arab tourists and the Malaysian tourist agencies should always consider personal and situational characteristics in planning for tourism adventure policies on tourism. Finally, the study highlights the limitation of the study and the suggestions for future study.